Extensive central nervous system cryptococcal disease presenting as immune reconstitution syndrome in a patient with advanced HIV: report of a case and review of management dilemmas and strategies - Onyema Ogbuagu; Merceditas Villanueva (MDPI AG, 2014)
One of the complications of the use of anti-retroviral therapy (ART), immune reconstitution inflammatory syndrome (IRIS), is particularly problematic in the management of cryptococcal meningitis. We present the case of a 35- year-old male with acquired immune deficiency syndrome diagnosed with extensive central nervous system (CNS) cryptococcal disease, including meningitis and multiple intracranial cysts, diagnosed eight weeks after the initiation of ART. The patient experienced a relapsing and remitting clinical course despite repeated courses of potent antifungal therapy and aggressive management of raised intracranial pressure. This review highlights therapeutic dilemmas and strategies in the management of CNS cryptococcosis complicated with IRIS and highlights gaps in available treatment guidelines.